The assemblage composition and structure of swimming crabs (Portunoidea) in continental shelf waters of southeastern Brazil - Andrade, Luciana Segura de; Frameschi, Israel F. [UNESP]; Costa, Rogério Caetano da [UNESP]; Castilho, Antonio Leão [UNESP]; Fransozo, Adilson [UNESP] (Elsevier, 2015)
Three regions along the Brazilian coast characterized by the occurrence of contrasting natural phenomena, such as upwellings and continental input, were surveyed to determine the composition and structure of the assemblage of swimming crabs. Twelve monthly collections were undertaken (July 2010 to June 2011) in Macaé, Rio de Janeiro (MAC); Ubatuba, São Paulo (UBA); and São Francisco do Sul, Santa Catarina (SFS). The lowest values ​​of the phi sediment grain size measure, bottom temperature and the highest values of organic matter and salinity were measured in MAC. In all, 10,686 individuals were collected, belonging to six species of Portunoidea: Arenaeus cribrarius, Callinectes danae, Callinectes ornatus, Callinectes sapidus, Achelous spinicarpus and Achelous spinimanus. A Multiple Response Permutation Procedure (MRPP) test indicated that the species composition differed significantly among the sampling sites, showing substantial heterogeneity in the composition and abundance of species among regions. The results suggest that C. danae was more abundant in waters with lower salinity and lower organic matter content. In contrast, A. spinimanus is positively correlated with these factors, showing a greater abundance under the opposite conditions. Callinectes ornatus appeared not to show strong selectivity for particular habitat characteristics. We conclude from these findings that areas affected by different phenomena produce changes in the composition and abundance of the assemblage of Portunoidea. Although the strength of eutrophication differs between UBA and MAC, the substantial continental inflow affecting SFS favors the development of species that complete their life cycle in the estuary.
Keywords: Biological structure; Continental waters; Decapoda; Dynamics of water masses